Equivalent uniaxial accelerogram for CSS-based isolation systems assessment under two-components seismic events. Issue 3 (3rd July 2017) - Furinghetti, Marco; Pavese, Alberto
ABSTRACT: Concave surface slider (CSS) devices represent an effective solution for base-isolation design problems. In such isolators the energy dissipation capability is induced by the sliding motions which occur at one or more sliding interfaces. The spherical shape of the sliding surfaces provides a significant recentering behavior, by means of the stepwise projection of the applied vertical load with respect to both horizontal directions. For two-components earthquake excitations, the recentering force is computed as a linear spring with respect to displacements along the main directions of motion; whereas, the frictional response is returned by the stepwise projection of the total frictional force, which is aligned with respect to the trajectory of the device: thus, a bi-axial interaction of the directions of motion has to be accounted for, when a friction-based device is modelled. However, available commercial software which can capture such a behavior are limited. In this work an analytical procedure is defined, for the computation of an "equivalent uniaxial accelerogram" for the seismic assessment of a base-isolated structure, subjected to a bi-directional earthquake. Thanks to the proposed theory, it is possible to compute a single ground acceleration time-history, related to a proper direction angle, which can reproduce the same effects of a two-components seismic event on a base-isolated structural system: the analogy between the equivalent uniaxial and the bi-directional events has been studied in terms of acceleration, velocity and displacement spectra respectively. Results for the base-isolated structure have been analyzed in terms of displacement, absolute acceleration and interstorey shear responses.